STRUKTUR KRISTAL DAN MORFOLOGI PERMUKAAN – SINTESIS SNO2 MENGGUNAKAN METODE SOL-GEL - Tri Arini; Latifa Hanum Lalasari; Iwan Setiawan; Lia Andriyah; Nadia Chrisayu Natasha; Fariza Eka Yunita; Ariyo Suharyanto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
SnO2 oxide powder was synthesized using the sol-gel method. SnO2 oxide powder was produced using a solution of tin(IV) chloride (SnCl4) and 25% ammonia (NH4(OH)) by annealing the final product for 4 hours at 900 °C. The pH variation was carried out at pH 7 and 9. XRD analysis showed that the structure of SnO2 formed was polycrystalline with a tetragonal crystal structure with crystal planes (110), (101); (200), (111), (210), (211), (220), (002), (310), (112), (301), (202), (321), (400), (222 ), (330) wherein the crystal plane (110) has the predominant structure. The crystal size using the Scherrer formula, varied from 56,204 and 54,936 nm for pH values ​​7 and 9. The size using HSP analysis, in the (110) plane the values ​​obtained were 561,594 and 543,901Å for pH 7 and 9. The crystal size decreased with increasing pH. Surface morphology was carried out by SEM analysis, obtained grain sizes of 71.5 and 62.32 nm at pH 7 and 9, respectively. The variation in pH mostly affected the size, shape, and morphology of SnO2.